Alteration of contrast enhanced ultrasound (CEUS) of hepatocellular carcinoma in patients with cirrhosis and transjugular intrahepatic portosystemic shunt (TIPS) - Chang, Johannes (Sci Rep, 2020)
Transjugular intrahepatic portosystemic shunt (TIPS) can treat portal hypertensive complications and modifies hepatic hemodynamics. Modification of liver perfusion can alter contrast enhancement dynamics of liver nodules. This study investigated the diagnostic performance of contrast-enhanced ultrasound (CEUS) to diagnose hepatocellular carcinoma (HCC) in cirrhosis with TIPS. In this prospective monocentric observational study, CEUS was used to characterize focal liver lesions in patients at risk for HCC with and without TIPS. Times of arterial phase hyperenhancement (APHE) und washout were quantified. Perfusion-index (PI) and resistance-index (RI) of hepatic artery and portal venous flow parameters were measured via doppler ultrasonography. Diagnostic gold standard was MRI/CT or histology. This study included 49 liver lesions [23 TIPS (11 HCC), 26 no TIPS (15 HCC)]. 26 were diagnosed as HCC by gold standard. Sensitivity and specificity of CEUS to diagnose HCC with and without TIPS were 93.3% and 100% vs. 90.9% and 93.3%, respectively. APHE appeared significantly earlier in patients with TIPS compared to patients without TIPS. TIPS significantly accentuates APHE of HCC in CEUS. CEUS has good diagnostic performance for diagnosis of HCC in patients with TIPS.